A Nanopipette Platform for Delivering Nanoliter Volumes of Acetylcholine. Issue 12 (1st August 2018) - McAllister, A. B.; Menchaca, C. X.; Freeman, J.; Chen, R.; Shen, M.
Abstract : Delivery of nano-liter volumes of neurotransmitter is important in fundamental studies to understand the brain function, as well as in pharmacological intervention for the treatment of neurological disorders. We present here a nanopipette based electrochemical delivery platform for the delivery of acetylcholine, and the measurement of the delivered acetylcholine concentration profile following its delivery. The delivery was enabled by the applied voltage and nano-liter volumes (1.342 ± 0.417 nL) of acetylcholine was successfully delivered. An acetylcholine sensing electrode was used to monitor the acetylcholine concentration in the cellular environment immediately following its delivery, based on the ion transfer across the interface between two immiscible electrolyte solutions (ITIES). Parameters that affect the delivery process were investigated and it was unveiled that both the applied voltage duration and voltage magnitude affect the acetylcholine delivery into the cellular medium. The presented nanoliter delivery platform has advantages of easiness to fabricate, low cost, and flexibility to be positioned over different types of cellular structure.